2005
DOI: 10.1177/0040517505054731
|View full text |Cite
|
Sign up to set email alerts
|

An Improved MWK Structure for Composite Reinforcement

Abstract: An improved MWK structure with a double loop pillar stitch is presented in this work. Its structural features, knitting process, and mechanical properties are analyzed and compared with a common tricot MWK structure. The results show that the improved MWK structure with the double loop pillar stitch has better mechanical properties than the common MWK structure with the tricot stitch.One current trend in textile structural composites is to extend their applications from secondary nonload-bearing structures to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
6
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 5 publications
0
6
0
Order By: Relevance
“…Theoretically, as many layers as preferred can be used but typical commercially available machines only allow four layers (Du and Ko, 1996). The purpose of the knit loops is to hold the layers of unidirectional yarns together, but it has also been proven to be the key to increasing the damage tolerance of the material (Zhou et al, 2005).…”
Section: Multiaxial Warp Knitsmentioning
confidence: 99%
See 1 more Smart Citation
“…Theoretically, as many layers as preferred can be used but typical commercially available machines only allow four layers (Du and Ko, 1996). The purpose of the knit loops is to hold the layers of unidirectional yarns together, but it has also been proven to be the key to increasing the damage tolerance of the material (Zhou et al, 2005).…”
Section: Multiaxial Warp Knitsmentioning
confidence: 99%
“…An improved MWK structure for composite reinforcement, developed by replacing the tricot stitch with a 'double loop pillar stitch', has been carried out by Zhou et al (2005) The modification has yielded improvements of up to 7% in breaking strength (Zhou et al, 2005). The tribology or wear resistance of MWK has also been investigated and has been shown to perform better than biaxial nonwoven structures (Mathew et al, 2007).…”
Section: Multiaxial Warp Knitsmentioning
confidence: 99%
“…For the multi-axial warp-knitted fabrics (MWKF), the following papers are found to be useful to discuss the fabric properties, such as the comparison analysis about the mechanical properties with different polymer-coated membranes or different inserted yarns [11][12][13] and also the manufacture and structure investigations [14,15]. Zhou et al [16] showed that the MWK structure with double loop pillar stitch was better than the common tricot stitch. Gao et al [17,18] studied the properties and meso-scale mechanism of MWK from different architectures, and found that the tear properties were dependent on the structures strongly.…”
Section: Introductionmentioning
confidence: 99%
“…This unique property of knitted fabrics limits their use as composite reinforcing elements. However, if yarns with high modulus are used in construction of knitted fabrics, then high quality composite materials can be made using these knitted fabrics [4,5]. In this respect, multi-axial warp knitted fabrics due to their inherent mechanical properties are preferred by composite designers.…”
Section: Introductionmentioning
confidence: 99%